Evaluation and comparison of in vitro antioxidant activities of unsaponifiable fraction of 11 kinds of edible vegetable oils. Issue 8 (11th October 2018) - Wang, Sujun; Yang, Ruinan; Li, Hui; Jiang, Jun; Zhang, Liangxiao; Zhang, Qi; Li, Peiwu
Abstract: The radical scavenging capabilities of the extracts from eleven edible vegetable oils were investigated by using 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), 2, 2′‐azino‐bis‐3‐ ethylbenzothiazoline‐6‐sulfonic acid (ABTS), and ferric reducing ability of plasma (FRAP) assays. The results indicated that rapeseed oil and sesame oil showed higher radical scavenging abilities than other vegetable oils. When the radical scavenging capabilities of the extracts from virgin camellia oils and commercially available refined camellia oils were evaluated by FRAP assay, the results showed that the antioxidant capabilities of the former were higher than the latter. Therefore, it is recommended that moderate refining processes should be taken to minimize the loss of antioxidant components and people consume virgin oils or less processed edible vegetable oils for higher antioxidant activities. Abstract : The radical scavenging capabilities of the extracts from eleven edible vegetable oils were investigated by using 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), 2, 2′‐azino‐bis‐3‐ ethylbenzothiazoline‐6‐sulfonic acid (ABTS), and ferric reducing ability of plasma (FRAP) assays. When the radical scavenging capabilities of the extracts from virgin camellia oils and commercially available refined camellia oils were evaluated by FRAP assay, the results showed that the antioxidant capabilities of the former were higher than the latter.